2020
DOI: 10.1186/s12912-020-00412-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between night shift work, eating habits and BMI among nurses in Lebanon

Abstract: Background: The objective of this cross-sectional study was to evaluate the relationships between night shift work, eating habits and body mass index (BMI) among Lebanese nurses. Methods: A total of 307 nurses were randomly selected from five hospitals located in Beirut. Data about demographic and professional characteristics, anthropometric measures, dietary habits and intakes were collected through a validated questionnaire. To study the relationship between night shift work, eating habits and BMI, chisquare… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 31 publications
4
29
0
3
Order By: Relevance
“…Moreover, the eating habits of Polish nurses with Type D personality were significantly worse than those with non-Type D (p = .001), which is in line with a previous study showing that those with Type D personality consume less healthy food and more fat and sugar, partly to cope with stress (Booth & Williams, 2015). Another major factor associated with poor eating habits and BMI is shift work (Samhat, Attieh, & Sacre, 2020). Therefore, educating nurses and nurse managers on the harmful health effects of night shift work, and the impact of Type D personality, and providing appropriate dietary guidance via nutritionists, may help reduce the risk of overweight and obesity.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, the eating habits of Polish nurses with Type D personality were significantly worse than those with non-Type D (p = .001), which is in line with a previous study showing that those with Type D personality consume less healthy food and more fat and sugar, partly to cope with stress (Booth & Williams, 2015). Another major factor associated with poor eating habits and BMI is shift work (Samhat, Attieh, & Sacre, 2020). Therefore, educating nurses and nurse managers on the harmful health effects of night shift work, and the impact of Type D personality, and providing appropriate dietary guidance via nutritionists, may help reduce the risk of overweight and obesity.…”
Section: Discussionsupporting
confidence: 86%
“…Thus, all these changes in the circadian clock are associated with temporal alteration in feeding behavior and increased weight gain, explaining the high proportion of obesity in night shift workers [115]. It seems also salient to note that night shift work is positively associated with abnormal eating patterns and BMI [116,117]. Then, dyslipidemia could be an epiphenomenon of snacking.…”
Section: The Deleterious Effect Of Permanent Night Shiftmentioning
confidence: 99%
“…In a discussion paper by Lowden et al [ 9 ], the authors observed that both meal content and timing are important for the nutritional management of night shift workers. More recently, previous studies have shown that energy metabolism exhibits circadian rhythms and that nutrient intake during the night may disrupt these rhythms [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings show that night workers tend to display poorer adherence to nutritional recommendations [ 9 ]. However, new evidence has suggested that controlling the timing of food intake represents a potential therapeutic approach in the context of preventing overweight and metabolic disorders [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%